Exploring the information flow and dissemination practices of the internally displaced persons in San Jose Del Monte Heights - Martinez, Jasmine G.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2019)
An important aspect of movement of the internally displaced persons are their access to information necessary for them, such as the cause of their displacement, job opportunities, schooling, and health concerns. This access to information is manifested in many ways such as information dissemination of the government agencies, and the information seeking behaviors of the people. These are what the study explored and tried to find out.

The objectives of this study are: (1) to evaluate the state of access to information of the internally displaced persons, (2) establish the information needs on the internally displaced persons, (3) to know the information seeking behavior of the internally displaced person during different phases of displacement, and (4) to analyze on to what extent to the government and other agencies disseminate information and its effectively to the displaced people. In this study, the area of focus is San Jose Del Monte Heights, a resettlement area of displaced people from the National Capital Region. Three groups of respondents, the information providers, the team leaders, and the general membership were interviewed.

It was found out that (1) there are efforts on both ends to gain and give to access to information to the people, but still full access is seemingly impossible to achieve. (2) The information needs of IDPs are the cause of displacement, service providers in the resettlement area, government programs, housing units, job security, and education. (3) For the information seeking behavior, some of the IDPs did not actively seeking information in initial displacement but are more eager now to access information in resettlement and post-resettlement stage. (4) Lastly, the National Housing Authority is confident with their information dissemination effort but is aware of the lack of information - complains of the people.

In conclusion, accessing information is a significant right and practice of the internally displaced persons because it is only through credible information can one make an informed decision that will help them with their displacement. It is, therefore, necessary that both the IDPs actively seek and use information, and the government and other agencies to effectively disseminate information and make sure that people can access it.
Thesis
Keywords: Internally displaced persons -- National Capital Region (Philippines)